Determination of Contributing Risk Factors to Adult Nephrolithiasis Patients - Reda, juma; Kadhim, Haleema (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: To determine the contributing risk factors to adult nephrolithiasis patients.Methodology: A descriptive study was conducted to determine the contributing risk factors toAdults nephrolithiasis starting from December 2007 to September 2008. A purposive "nonprobability"sample of (100) patients with nephrolithiasis was selected of those who wereadmitted to the hospitals, attending the Urology Consultation Clinic and Extracorporeal ShockWave Lithotripsy Department. The study instrument consists of two parts. The first part isrelated to the patients' demographic variables and the second part is constructed to serve thepurpose of the study. The total number of items in the questionnaire was (85) ones.Content Validity of the instrument was determined through the use of a panel of (12) expert inthe field of the study. Reliability of the instrument was estimated through the pilot study. Datawere analyzed through descriptive data analysis and the inferential data analysis approaches.